1999
DOI: 10.1016/s0741-5214(99)70007-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graded compression elastic stockings on the lower leg venous system during daily activity

Abstract: Graded compression elastic stockings help preserve lower leg venous caliber and tone throughout the deep, superficial, and perforating venous systems during normal ambulatory activity, and this may, in part, explain their beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…The Effect of Surgery and Compression on Healing and Recurrence (ESCHAR) trial 1 was one of the first large studies that explored the potential benefit of compression plus surgery for ulcer healing, which concluded that there was no significant difference in healing rate with the addition of surgery, compared with historic studies that advocated compression therapy alone 11 in treating venous reflux. 12,13 Recent trials comparing surgery plus compression with compression alone, although large in patient numbers, lack applicability to all CEAP 6 patients because most patients underwent only saphenous vein ablation despite the presence of perforator reflux. 3,6 Elimination of perforator reflux combined with ablation of incompetent superficial veins, which was not included in the ESCHAR trial, has recently been reported to facilitate an increase in ulcer healing over ablation of incompetent superficial veins alone.…”
Section: Discussionmentioning
confidence: 99%
“…The Effect of Surgery and Compression on Healing and Recurrence (ESCHAR) trial 1 was one of the first large studies that explored the potential benefit of compression plus surgery for ulcer healing, which concluded that there was no significant difference in healing rate with the addition of surgery, compared with historic studies that advocated compression therapy alone 11 in treating venous reflux. 12,13 Recent trials comparing surgery plus compression with compression alone, although large in patient numbers, lack applicability to all CEAP 6 patients because most patients underwent only saphenous vein ablation despite the presence of perforator reflux. 3,6 Elimination of perforator reflux combined with ablation of incompetent superficial veins, which was not included in the ESCHAR trial, has recently been reported to facilitate an increase in ulcer healing over ablation of incompetent superficial veins alone.…”
Section: Discussionmentioning
confidence: 99%
“…20 Under normal circumstances, the greatest diameter of the common femoral vein is approximately 16 mm, 21 the popliteal vein is 8 mm, 21 and the posterior tibial vein 4 mm. 22 Therefore, for a given amount of blood being ejected from, for instance, the foot, the velocities achieved would be expected to be higher in the posterior tibial vein than the femoral. However, the velocity must also depend on the part of the limb compressed, since the plantar venous plexus within the foot holds a smaller volume of blood than the calf and thigh.…”
Section: What Effect Do Intermittent Compression Systems Have On Venomentioning
confidence: 99%
“…9,22 Age, gender, pregnancy, genetics are all risk factors for the CVI development, together with exposure to gravity for working reason. However, only the latter is a modifiable risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…8 Elastic stockings compression therapy was first introduced in the fifties: it remains the most widely accepted treatment of CVI. 9 Particularly, by means of air plethysmography a significant improvement of venous functional parameters with elastic stockings has been demonstrated. 10 Looking at the literature, good evidences for the use of compression can be found for some clinical indications, even if little is known about the specific dosimetry, timing and type of compression to be applied.…”
Section: Introductionmentioning
confidence: 97%